Bioengineering of fungal endophytes through the CRISPR/Cas9 system - Verma, Vinita; Batta, Arpita; Singh, Harikesh B.; Srivastava, Alok; Garg, Sanjay Kumar; Singh, Vijay Pal; Arora, Pankaj Kumar (Frontiers in Microbiology, 2023)
The CRISPR/Cas9 system is a genome-editing tool that allows for precise and efficient modifications to the DNA of a cell. This technology can be used in endophytic fungi, which live within plants and can have beneficial effects on their host, making them important for agriculture. Using CRISPR/Cas9, researchers can introduce specific genetic changes into endophytic fungal genomes, allowing them to study the function of genes, improve their plant-growth-promoting properties, and create new, more beneficial endophytes. This system works by using the Cas9 protein, which acts as a pair of molecular scissors, to cut DNA at specific locations determined by a guide RNA. Once the DNA is cut, the cell’s natural repair mechanisms can be used to insert or delete specific genes, allowing for precise editing of the fungal genome. This article discusses the mechanism and applications of CRISPR/Cas9 to fungal endophytes.